Β‐Dicalcium silicate‐based cement: Synthesis, characterization and in vitro bioactivity and biocompatibility studies. Issue 10 (12th December 2013) - Correa, Daniel; Almirall, Amisel; García‐Carrodeguas, Raúl; Alberto dos Santos, Luis; De Aza, Antonio H.; Parra, Juan; Ángel Delgado, José
Abstract β‐dicalcium silicate (β‐Ca2SiO4, β‐C2S) is one of the main constituents in Portland cement clinker and many refractory materials, itself is a hydraulic cement that reacts with water or aqueous solution at room/body temperature to form a hydrated phase (C‐S‐H), which provides mechanical strength to the end product. In the present investigation, β‐C2S was synthesized by sol–gel process and it was used as powder to cement preparation, named CSiC. In vitro bioactivity and biocompatibility studies were assessed by soaking the cement samples in simulated body fluid solutions and human osteoblast cell cultures for various time periods, respectively. The results showed that the sol–gel process is an available synthesis method in order to obtain a pure powder of β‐C2S at relatively low temperatures without chemical stabilizers. A bone‐like apatite layer covered the material surface after soaking in SBF and its compressive strength (CSiC cement) was comparable with that of the human trabecular bone. The extracts of this cement were not cytotoxic and the cell growth and relative cell viability were comparable to negative control. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3693–3703, 2014.